Dynamics of Organizational Climate, Leadership, and Job Satisfaction in Increasing Employee Productivity at the Langsa Baro Sub-district Office, Langsa City - Harahap, Parlin Muda; Nasution, Abdul Haris; Gunawan, Ari; Asmiati, Asmiati; Hidayat, Taufik; Supriadi, Supriadi (Mahesa Research Center, 2025)
This study aims to analyze the relationship between organizational climate, leadership, and job satisfaction in increasing employee productivity at the Langsa Baro Sub-district Office, Langsa City. This study uses a qualitative approach with a case study method. Data were collected through in-depth interviews, observations, and documentation, which were then analyzed thematically. The results of the study show that a supportive organizational climate, good interpersonal relationships, and a conducive work atmosphere contribute positively to employee productivity. The participatory leadership style applied by the leadership increases employee involvement, although under certain conditions it is still found that the application of authoritarian styles that cause dissatisfaction is still found. Employee job satisfaction levels are in the moderate category, with the main complaints related to salary, incentives, and career development opportunities. Overall, it was found that organizational climate, leadership, and job satisfaction are interrelated in influencing employee productivity. This research suggests the need to strengthen vertical communication, policy transparency, and human resource management strategies to optimize employee productivity in the government sector